2017
DOI: 10.1111/jpi.12453
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates low PS I‐limited carbon assimilation under elevated CO2 and enhances the cold tolerance of offspring in chlorophyll b‐deficient mutant wheat

Abstract: Melatonin is involved in the regulation of carbohydrate metabolism and induction of cold tolerance in plants. The objective of this study was to investigate the roles of melatonin in modulation of carbon assimilation of wild-type wheat and the Chl b-deficient mutant ANK32B in response to elevated CO 2 concentration ([CO 2 ]) and the transgenerational effects of application of exogenous melatonin (hereafter identified as melatonin priming) on the cold tolerance in offspring. The results showed that the melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 66 publications
9
68
0
1
Order By: Relevance
“…It has been shown that melatonin can preserve chlorophyll and improve the photosynthetic efficiency in plants under stressful conditions (Yin et al , Zhao et al , Jiang et al , Li et al ). Consistent with these findings, our results indicated that 100 μM melatonin application significantly improved the levels of qP and ΦPSII under NaCl stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that melatonin can preserve chlorophyll and improve the photosynthetic efficiency in plants under stressful conditions (Yin et al , Zhao et al , Jiang et al , Li et al ). Consistent with these findings, our results indicated that 100 μM melatonin application significantly improved the levels of qP and ΦPSII under NaCl stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts affect the localization of numerous receptors and signaling proteins, and therefore have a strong influence on multiple signal transduction cascades (Cao et al, ; Jeelani et al, ). For instance, lipid rafts play a vital role in LPS receptor (TLR4) and TGF‐β receptor‐mediated signal transduction (Kanwar et al, ; X. Li, Brestic, et al, ). Activation of the Wnt/β‐catenin pathway is facilitated by the localization of LRP6 in lipid rafts (Nedic Erjavec et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, AMP-activated protein kinase; CREB, cAMP-response element-binding protein; Mfn2, Mitofusin-2; NC, negative control; ox-LDL, oxidized low-density lipoprotein; PTEN, phosphatase and tensin homolog. *p<.05 versus control group, # p<.05 versus ox-LDL + si-NC group, @ p<005 versus ox-LDL + si-PTEN group vital role in LPS receptor (TLR4) and TGF-β receptor-mediated signal transduction (Kanwar et al, 2018;X. Li, Brestic, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SNAT is highly conserved in plant species ranging from cyanobacteria to higher plants, indicative of the essential role of SNAT in melatonin synthesis and offering indirect evidence of the omnipresence of melatonin in the plant kingdom. The few plants tested so far containing undetectable levels of melatonin possess SNAT genes in their genomes, suggesting that these plants also have the capacity to synthesize low levels of melatonin …”
Section: Introductionmentioning
confidence: 99%